2001
DOI: 10.1590/s1415-43662001000100007
|View full text |Cite
|
Sign up to set email alerts
|

Comparação da evapotranspiração real simulada e observada em uma bacia hidrográfica em condições naturais de cerrado

Abstract: Através deste trabalho, objetivou-se: (i) simular a evapotranspiração real de uma microbacia sob vegetação natural de cerrado, ao longo de um ano, compreendido entre os dias 04/08/98 e 03/08/99; (ii) comparar e analisar o comportamento da evapotranspiração real, do escoamento total e da lâmina de água armazenada no solo, através dos valores medidos e simulados. Utilizando-se a equação do balanço hídrico, determinou-se a evapotranspiração real total do período (830,53 mm) ao longo do qual foram efetuadas mediçõ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 2 publications
(2 reference statements)
1
3
0
7
Order By: Relevance
“…Há grande demanda de informações sobre a dinâmica da infiltração de água no solo para trabalhos que envolvam, por exemplo, a estimativa da erosão do solo (Borselli et al, 2001), produção de sedimentos (Holden & Burt, 2002;Nadal-Romero & Regüés, 2009), transferência de solutos na paisagem (Chaplot & Poesen, 2012), disponibilidade de água para as plantas (Anderson et al, 2009), evapotranspiração (Lima et al, 2001) e recarga de aquíferos (Cunha & Wendland, 2005;Munz et al, 2011).…”
Section: Introductionunclassified
“…Há grande demanda de informações sobre a dinâmica da infiltração de água no solo para trabalhos que envolvam, por exemplo, a estimativa da erosão do solo (Borselli et al, 2001), produção de sedimentos (Holden & Burt, 2002;Nadal-Romero & Regüés, 2009), transferência de solutos na paisagem (Chaplot & Poesen, 2012), disponibilidade de água para as plantas (Anderson et al, 2009), evapotranspiração (Lima et al, 2001) e recarga de aquíferos (Cunha & Wendland, 2005;Munz et al, 2011).…”
Section: Introductionunclassified
“…The altitude variation is associated with precipitation, evaporation and transpiration, and consequently it has an influence on the average runoff. Large variations in altitude in a watershed cause significant differences in average temperature, which may give rise to variations in evapotranspiration (Lima et al, 2001); (v) Order: the order of watercourses was determined following the criteria established by Strahler (1957), in which no tributary canals are characterized as first order. Second-order canals are those stemming from the confluence of two first-order canals and may have tributaries of the first order.…”
Section: Methodsmentioning
confidence: 99%
“…The crop coefficient of the pasture varied between 0.56 and 0.81, close to that of Capim-Elefante (Pennisetum purpureum) as described by Muniz et al [62], which obtained an average Kc between 0.45 and 0.78, and also close to Capim-Tanzânia (Panicum maximum) as described by Bueno et al (2009), which obtained an average Kc between 0.5 and 0.98 in the southeast Brazil region. Lima et al [63] found crop coefficient values for forest ("Cerrado") between 1.00 and 1.10. Figure 10 shows the relationship between mean values of crop coefficient (ET r ) and accumulated degree-days (DDac) in the sugarcane crops in the studied period.…”
Section: Crop Coefficientmentioning
confidence: 99%